2014
DOI: 10.1186/1471-2407-14-261
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of family history-based colorectal cancer screening in Australia

Abstract: BackgroundWith 14.234 diagnoses and over 4047 deaths reported in 2007, colorectal cancer (CRC) is the second most common cancer and second most common cause of cancer-related mortality in Australia. The direct treatment cost has recently been estimated to be around AU$1.2 billion for the year 2011, which corresponds to a four-fold increase, compared the cost reported in 2001. Excluding CRCs due to known rare genetic disorders, 20% to 25% of all CRCs occur in a familial aggregation setting due to genetic varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…It demonstrated that in people at increased risk due to a strong family history of CRC, five yearly colonoscopy cost Au$12,405 per year gained, with an average life expectancy of 16.1 years 26.…”
Section: Discussionmentioning
confidence: 99%
“…It demonstrated that in people at increased risk due to a strong family history of CRC, five yearly colonoscopy cost Au$12,405 per year gained, with an average life expectancy of 16.1 years 26.…”
Section: Discussionmentioning
confidence: 99%
“…A few earlier studies have examined the cost-effectiveness of colonoscopic surveillance or colonoscopic screening based on family history [11][12][13][14][15]. All these studies conclude colonoscopy is a cost-effective method to prevent inherent CRC.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few cost-effectiveness studies published on colonoscopic surveillance for individuals with inherent risk for CRC [11][12][13][14][15]. These studies are all based on simulation models and not on the outcome of a real cohort undergoing surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…26,[37][38][39][40][41][42][43] Some reported that screening based on FS was the most cost-effective, [37][38][39] whilst other studies found that colonoscopy screening had greater cost-effectiveness. 26,40,41 Yet one study reported that a hybrid method using yearly rehydrated faecal occult blood tests coupled with FS was amongst the most cost-effective. 42 Our study is novel and unique as it is based on age and gender, and the data were from observations from actual screening practices.…”
Section: Discussionmentioning
confidence: 99%